2022
DOI: 10.1093/geronb/gbac001
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Disabilities and Social Isolation Among Hispanic Older Adults: Toward Culturally Sensitive Measurement of Social Isolation

Abstract: Objectives Sensory disabilities, including vision disability and hearing disability, increase risk for social isolation, which is associated with multiple negative health outcomes. Existing literature suggests that the cultural value of familism may provide a buffer against social isolation. We examined the longitudinal trajectory of social isolation among Hispanic older adults with self-reported vision disability (SRVD) and self-reported hearing disability (SRHD) and tested a modified measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…We measured social isolation with the goal of identifying elements of familial and other support that might be more relevant to Hispanic individuals [32]. Social isolation scores were calculated by aggregating each of the following possibilities, with "yes" coded as 1 and "no" coded as 0 for each of the following: (a) living alone; (b) having one or fewer people who he/she talked to in the last year about important things; (c) not attending religious services; (d) not visiting friends/family in the participant's home or in the home of the friend/family member; and (e) not living in an intergenerational household.…”
Section: Social Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…We measured social isolation with the goal of identifying elements of familial and other support that might be more relevant to Hispanic individuals [32]. Social isolation scores were calculated by aggregating each of the following possibilities, with "yes" coded as 1 and "no" coded as 0 for each of the following: (a) living alone; (b) having one or fewer people who he/she talked to in the last year about important things; (c) not attending religious services; (d) not visiting friends/family in the participant's home or in the home of the friend/family member; and (e) not living in an intergenerational household.…”
Section: Social Isolationmentioning
confidence: 99%
“…Terms that describe this primacy of the family include communalism in African cultures, filial piety in Asian Cultures, and familism among Hispanic cultures [30]. Hispanics may prefer to receive social support from family rather than from community resources [31,32]. Past research has identified a link between the cultural value of familism and perceived social support as well as psychological well-being, social well-being, and reduced distress [30,33].…”
Section: Introductionmentioning
confidence: 99%